2023
DOI: 10.1038/s41467-023-37965-0
|View full text |Cite
|
Sign up to set email alerts
|

Nickel/biimidazole-catalyzed electrochemical enantioselective reductive cross-coupling of aryl aziridines with aryl iodides

Abstract: Here, we report an asymmetric electrochemical organonickel-catalyzed reductive cross-coupling of aryl aziridines with aryl iodides in an undivided cell, affording β-phenethylamines in good to excellent enantioselectivity with broad functional group tolerance. The combination of cyclic voltammetry analysis of the catalyst reduction potential as well as an electrode potential study provides a convenient route for reaction optimization. Overall, the high efficiency of this method is credited to the electroreducti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(14 citation statements)
references
References 89 publications
0
14
0
Order By: Relevance
“…Inspired by the Doyle group's reaction design, the groups of Milo and Mei devised an electrochemical enantioselective nickel‐catalyzed reductive cross‐coupling (Scheme 11). [29] This transformation enables electrophilic cross‐coupling of arylaziridines with (hetero)aryl iodides at the benzylic position to afford β‐(hetero)arylethylamines in synthetically useful yields (40–95 %) and enantiomeric excesses up to 94 %. Mechanistic studies with cyclic voltammetry suggest that under their standard reaction conditions, a Ni 0 species can undergo oxidative addition with aryl iodides but not with aziridines.…”
Section: Ring‐opening Of Aziridinesmentioning
confidence: 99%
“…Inspired by the Doyle group's reaction design, the groups of Milo and Mei devised an electrochemical enantioselective nickel‐catalyzed reductive cross‐coupling (Scheme 11). [29] This transformation enables electrophilic cross‐coupling of arylaziridines with (hetero)aryl iodides at the benzylic position to afford β‐(hetero)arylethylamines in synthetically useful yields (40–95 %) and enantiomeric excesses up to 94 %. Mechanistic studies with cyclic voltammetry suggest that under their standard reaction conditions, a Ni 0 species can undergo oxidative addition with aryl iodides but not with aziridines.…”
Section: Ring‐opening Of Aziridinesmentioning
confidence: 99%
“…BiIM ligands are more electron-rich than Biox ligands, which can improve the catalyst reactivity in electrochemical conditions. 84 In addition, when N,N-dimethylacetamide (DMAc) was used as the solvent instead of acetone, both the yield and ee value decreased (entry 7). We also used Al or Zn as the anode instead of Fe, which resulted in low yields (entries 8 and 9).…”
mentioning
confidence: 99%
“…Recently, we have witnessed the renaissance of synthetic organic electrochemistry because of its tunability, sustainability, and scalability. In addition, the merging of electrochemistry with transition metal catalysis has become a promising approach for organic synthesis because the reaction selectivity, including enantioselectivity, can be governed by catalysts via ligand modifications. In this context, enantioselective nickel-catalyzed electroreductive cross-couplings (eRCCs) have emerged as an effective strategy for asymmetric transformation in which low-valent nickel species are regenerated upon cathodic reduction, as demonstrated by the groups of Reisman, Mei, and Nevado (Scheme b) . Very recently, Rueping et al described electrochemical chemo- and regioselective arylalkylation, dialkylation, and hydro­(deutero)­alkylation of 1,3-enynes in the presence of a nickel catalyst .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…As we know, Lewis acid or Lewis base-catalyzed nucleophilic ring opening of aryl aziridines has been well established for synthesizing arylethylamines . In recent decades, the transition-metal-catalyzed cross-coupling of arylaziridines has proven to be another attractive platform for highly efficient and selective synthesis of arylethylamines (Scheme A). , For instance, Doyle et al ,,, has disclosed that the Ni-catalyzed Negishi coupling of arylaziridines with aliphatic/aryl organozinc reagents could produce arylethylamines efficiently. Minakata and Takeda et al have reported a Pd-catalyzed enantiospecific and regioselective Suzuki–Miyaura coupling of arylaziridines with arylboronic acids to synthesize enantioenriched arylethylamines.…”
mentioning
confidence: 99%